Characteristics of gallstones in Uruguay - Delgado, Bolivar; Perrier, José (Cirugía del Uruguay, 1979)
On the basis of case material covering a series of 350 biliary lithiasis operations, the author reviews the characteristics of this condition in our country and compares them with tho'se of other authors. The type of calculi found and pathologic circumstances involved, deserve special attention.